The proepicardium keeps a potential for glomerular marker expression which supports its evolutionary origin from the pronephros. Issue 4 (July 2015) - Cano, Elena; Carmona, Rita; Velecela, Víctor; Martínez‐Estrada, Ofelia; Muñoz‐Chápuli, Ramón
SUMMARY The proepicardium is the embryonic primordium of the epicardium. This transient structure is essential for cardiac development giving rise to the epicardium and supplying the heart with vascular and cardiac connective tissue progenitors. However, their nature and evolutionary origin are poorly‐known. We have suggested elsewhere (Pombal et al. Evol. Dev. 10: 210–216, 2008; Cano et al., J. Dev. Biol. 1: 3–19, 2013) that the proepicardium is an evolutionary derivative of the primordium of an ancient external pronephric glomerulus, devoid of its original excretory function. In this study, we describe for the first time expression of two podocyte markers in the chick proepicardium (glepp1 and synaptopodin) and we have shown how these podocyte markers as well as the intermediate mesoderm marker Pax2 are strongly upregulated when the proepicardium is cultured with nephrogenic inducers. Retinoic acid treatment also induced in the proepicardium expression of Hoxb4, a gene which confers to intermediate mesoderm competence to respond to nephrogenic signals. Thus, a latent nephrogenic potential persists in the proepicardium and also that its original glomerular fate can be partially rescued. The transcription factor Wt1, essential for kidney and epicardial development, plays opposite roles in both tissues, inducing epithelial‐mesenchymal transition in the proepicardium and promoting epithelialization in the kidneys (Essafi et al., Dev. Cell 21: 559–574, 2011). Consistently with this antithetical function of Wt1, we have observed an upregulation of podocalyxin in the epicardium of mouse embryos with conditional deletion of the Wt1 gene, while this protein is transcriptionally activated by Wt1 in podocytes.